HEPATITIS B INFECTION: A SURVEY OF AWARENESS AND PREVALENCE AMONG MEDICAL LABORATORY PROFESSIONALS - Mbah, Chidinma Uchechi; Eze, Ngozi Chukwudi; Okafor, Emeka Uchenna (American Journal of Public Health and Epidemiology (AJPHE), 2023)
Viral hepatitis, a necro-inflammatory liver disease, poses a significant public health challenge worldwide, particularly in developing countries. This condition is primarily caused by the hepatitis B virus (HBV), a 42nm DNA virus from the hepadnaviridae family. HBV infection can manifest in both acute and chronic forms, and it is highly contagious, primarily transmitted through contact with infectious blood or body fluids. Transmission can occur through percutaneous routes, such as needle pricks, or permucosal exposure via direct contact with mucous membranes or non-intact skin. Additionally, it can result from exposure to contaminated surfaces, unprotected sexual contact, sharing of needles among intravenous drug users, needle injuries, and transfusion of contaminated blood. Vertical transmission from mother to child during birth is another common mode of HBV infection. The consequences of HBV infection are severe and can lead to the development of liver cirrhosis, hepatocellular carcinoma (HCC), and various other liver-related diseases. This paper provides an overview of the global burden of hepatitis B and its impact on public health, with a focus on developing countries. The incidence and prevalence of HBV infection in these regions are significantly higher, making it a pressing concern for policymakers, healthcare providers, and researchers alike. Understanding the dynamics of HBV transmission, risk factors, and the clinical outcomes of infection is crucial for designing effective prevention and control strategies